2014
DOI: 10.1517/14656566.2014.903925
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of bone metastases in breast cancer patients – an update

Abstract: Despite the potent osteoclast inhibiting effects of the bone-targeted agents in current clinical use, we have likely maximized their ability to inhibit SREs and must in turn focus on minimizing their potential toxicity. The future will likely involve more novel treatment strategies as well as the development of new agents. The current 'one size fits all' approach for the management of breast cancer bone metastases will be replaced by 'tailored' treatment for each individual patient as we usher in the era of 'p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Most osteolytic factors stimulate osteoclast bone resorption and consequently decreasing the survival rates of breast cancer patients [21]. Therefore, bisphosphonates (anti-bone resorptive agents) and denosumab (a monoclonal antibody against RANKL), which were primarily developed as therapeutic agents for osteoporosis, have been used in therapy for patients with bone metastatic breast cancer [9,36]. Platycodin D noticeably suppressed the number of multinucleated osteoclasts in the BMMs that were treated with RANKL and the osteoclast-mediated formation of the resorption pit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most osteolytic factors stimulate osteoclast bone resorption and consequently decreasing the survival rates of breast cancer patients [21]. Therefore, bisphosphonates (anti-bone resorptive agents) and denosumab (a monoclonal antibody against RANKL), which were primarily developed as therapeutic agents for osteoporosis, have been used in therapy for patients with bone metastatic breast cancer [9,36]. Platycodin D noticeably suppressed the number of multinucleated osteoclasts in the BMMs that were treated with RANKL and the osteoclast-mediated formation of the resorption pit.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have paid much attention to osteoclast-targeting agents with high potential for the treatment of cancer patients with bone metastases [7,8]. In the clinic, anti-bone resorptive drugs blocking the differentiation and activation of osteoclasts are used to treat skeletal-related events by breast cancer metastases, and these agents have increased the quality of life of patients [9]. However, these treatments do not improve patient survival, likely because they are not effective in directly counteracting tumor cell expansion and cause adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Group Bone Metastases Module (EORTC QLQ BM22) is a bone metastases- specific instrument that measures the impact of bone metastases on patients’ quality of life. It has been extensively validated internationally and is well-suited to use within clinical trials [24] .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review evaluating de-escalated treatment (i.e. every 12 weeks) of breast cancer patients with bone-targeted agents in comparison to current standard practice of every 3–4 weeks showed a clear knowledge gap with regard to establishing the clinical benefits of de-escalated bone targeted agent therapy in metastatic breast cancer patients [24] . Similarly, a recent systematic review also demonstrated that denosumab 12-weekly was as effective as 4-weekly dosing in patients with bone metastases from prostate cancer (“in press”).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades bone oncology research has tended to focus on the mechanisms of bone destruction when tumour cells are present [1], [2], [3]. The realisation of the important interplay between the tumour cell, the bone microenvironment and the osteoclast in particular led to the rapid expansion of clinical studies with bone-targeting agents, such as bisphosphonates and denosumab [4], [5].…”
Section: Introductionmentioning
confidence: 99%